Korean Public Bathhouse: Potential of Interiority - Huh, Michelle Boyoung (Interiority, 2023)
This essay introduces the Korean public bathhouse, jjimjil-bang, to understand the concept of interiority from sociocultural and psychological perspectives. The author addresses interiority as a continuous process of defining the range of intimacy that changes with context, space, and time. Interiority involves individuating spatial and situational moments in the blended physical, perceived, and imaged environment. In exploring interiority, the case of jjimjil-bang suggests broad perspectives for understanding spatial circumstances as an integration of the activity, environment, and situation. The author introduces the characteristics of jjimjil-bang in terms of the program, spatial structure, and meaning of memory. To demonstrate the potential of interiority, the concepts of private-public, interiority-exteriority, inclusivity-exclusivity, closeness-openness, and the quotidian issue are discussed. Consequently, the author highlights the individual's subjectivity of spatial perception, the desire for intimacy, and the individual's engagement in shaping interiority. Thus, the range of interiority is expanded from self to outworld beyond the physical space.